Pancasila dalam Tata Kelola Ekonomi Digital Global: Studi Hukum Internasional terhadap Perdagangan Elektronik - Naisyila Desnita Cahayani Saputra; Putri Agustin Sulistyowati; Fatimah Nur Azizah; Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Indonesia's digital economy is rapidly growing with the emergence of e-commerce, fintech, and blockchain technology that facilitate cross-border transactions. However, challenges such as technological access inequality, personal data exploitation, and multinational company dominance remain major concerns. Therefore, implementing Pancasila values in digital economy governance is crucial to ensuring social justice, consumer protection, and national competitiveness. Pancasila principles, such as moral-based business ethics, consumer rights protection, digital sovereignty, and participatory regulation, must be integrated into digital economic policies. Additionally, electronic commerce regulations based on international law should align with national interests to balance digital economic growth and constitutional rights protection. Thus, Pancasila-based digital economic policies can promote inclusivity, strengthen SMEs' competitiveness, and ensure the broader welfare of society.